Positive Impact of a Point-of-Care Molecular Influenza Test in the Emergency Department During the 2017–2018 Seasonal Influenza Epidemic. (31st July 2019) - Martinot, Martin; Greigert, Valentin; Gravier, Simon; Klein, Stephane; Eyriey, Magali; Pachart, Anne; Kaiser, Jean-Daniel; Zadeh, Mahsa Mohseni; De Briel, Dominique; Gottwalles, Yannick; Thibaud, Eric
Abstract: During the 2017–2018 flu epidemic, the point-of-care Alere-i (n = 72) and reverse transcription polymerase chain reaction (n = 106) tests were compared. Patients in the point-of-care group were administered oseltamivir significantly more rapidly (9 hours vs 23 hours), they spent less time in the emergency department, and they had lower rates of antibiotic administration and hospitalization.